An accuracy-enhanced cost model for virtual machine migration. (2018) - Zhang, Tienan
In cloud platforms, virtual machine migration has become an important service which enables cloud providers to apply various resource management policies. However, the cost of migrating a virtual machine still remains high even by using the most efficient migration algorithm. More importantly, many studies have indicated that improperly using migration service will lead to significantly performance degradation. In this paper, we present a cost model for quantitatively evaluate the cost of virtual machine migration with aiming at providing an accurate and effective approach to improving the efficiency of current migration service. The proposed model only relies on the information that can be easily obtained from the underlying virtualisation platform. To investigate the effectiveness and accuracy of the cost model, plenty of experiments are conducted by using various of standard benchmarks. The results show that it can significantly improve the accuracy comparing with existing models.